UPAYA RENEGOSIASI INDONESIA DALAM KERJA SAMA PENGEMBANGAN JET TEMPUR KOREAN FIGHTER XPERIMENT/INDONESIAN FIGHTER XPERIMENT (KFX/IFX) TAHUN 2018 - 2020 - Ajeng Rianti Nisita Hanityo, (2022)
Indonesia and South Korea carried out defense cooperation, namely the development of the Korean Fighter Xperiment/Indonesian Fighter Xperiment fighter jets. However, in the process this cooperation encountered several obstacles such as cost-share and work-share constraints. In order for the cooperation to continue, President Joko Widodo then instructed a small team which was then assigned to carry out renegotiation efforts with South Korea. This study aims to determine Indonesia's negotiation process in fighter jet development cooperation (KFX/IFX) in 2018 - 2020. The research method used in this study is descriptive qualitative and uses primary and secondary data sources. Data collection techniques are using interview techniques and literature or literature studies. The final result of this research is that Indonesia's renegotiation efforts in the cooperation to develop KFX/IFX fighter jets have succeeded in producing several mutual agreements with South Korea.